Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 6 - Review - Page 474: 49


$6xy (x+2)(x^2-2x+4)$

Work Step by Step

$6x^4y + 48xy = 6xy (x^3 + 8) =6xy (x^3 + 2^3) = 6xy (x+2)(x^2-2x+2^2)=6xy (x+2)(x^2-2x+4)$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.